Pengaruh Perbedaan Dosis Ekstrak Kunyit Merah (Curcuma domestica) Terhadap Perubahan Morfologi Ikan Nila (Oreochromis niloticus) yang Diinfeksi Bakteri Aeromonas hydrophila - WaOde Safia; Budiyanti; Riki Purnomo; Nurmita (FPIK UNIDAYAN, 2023)
The purpose of this study was to determine the ability of red turmeric extract doses to change the morphology of tilapia (Oreochromis niloticus) infected with Aeromonas hydrophila bacteria. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. Treatment A concentration of 0 ml of turmeric extract, treatment B concentration of 10 ml of turmeric extract, treatment C concentration of 15 ml of turmeric extract, and treatment D concentration of 20 ml of turmeric extract. From the results of observations for changes in fish morphology, changes in behavior, survival rates, water quality, and physical characteristics of the Aeromonas hydrophila bacteria, the data were analyzed descriptively in the form of tables and figures. The results showed that the ability of red turmeric extract was able to heal and inhibit Aeromonas hydrophila bacteria. This can be seen from the healing rate and changes in the morphology of tilapia (Oreochromis niloticus), where the wound is getting smaller even a few days after the injection the scar on the fish is not visible or closed. The highest survival rate for tilapia was in treatment B with a concentration of 10 ml of turmeric extract of 73.3%. Water quality parameters can still be tolerated by tilapia.